2021
DOI: 10.1038/s41467-020-20836-3
|View full text |Cite|
|
Sign up to set email alerts
|

Continent-wide tree fecundity driven by indirect climate effects

Abstract: Indirect climate effects on tree fecundity that come through variation in size and growth (climate-condition interactions) are not currently part of models used to predict future forests. Trends in species abundances predicted from meta-analyses and species distribution models will be misleading if they depend on the conditions of individuals. Here we find from a synthesis of tree species in North America that climate-condition interactions dominate responses through two pathways, i) effects of growth that dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 67 publications
(110 citation statements)
references
References 67 publications
1
94
0
Order By: Relevance
“…Widely available data on forest growth and mortality have allowed a good understanding of how tree growth and survival respond to climate fluctuations (Berdanier & Clark, 2016;Brienen et al, 2020;Manzanedo et al, 2020;McMahon et al, 2010;Young et al, 2017). By contrast, an understanding of climate change impacts on fecundity is less developed, as seed production is not directly observed for most species and habitats, and data accumulate slowly and with substantial investment (Clark et al, 2021;Kunstler et al, 2021). Thus, realistic estimates of tree fecundity and population growth rate are basically absent from most vegetation models (Kunstler et al, 2021;McDowell et al, 2020;Vacchiano et al, 2018).…”
Section: Synchrony Of Interannual Variation In Reproduction In Europeanmentioning
confidence: 99%
See 2 more Smart Citations
“…Widely available data on forest growth and mortality have allowed a good understanding of how tree growth and survival respond to climate fluctuations (Berdanier & Clark, 2016;Brienen et al, 2020;Manzanedo et al, 2020;McMahon et al, 2010;Young et al, 2017). By contrast, an understanding of climate change impacts on fecundity is less developed, as seed production is not directly observed for most species and habitats, and data accumulate slowly and with substantial investment (Clark et al, 2021;Kunstler et al, 2021). Thus, realistic estimates of tree fecundity and population growth rate are basically absent from most vegetation models (Kunstler et al, 2021;McDowell et al, 2020;Vacchiano et al, 2018).…”
Section: Synchrony Of Interannual Variation In Reproduction In Europeanmentioning
confidence: 99%
“…The capacity of future forests to support biodiversity and deliver ecosystem services depends on regeneration that tracks 21st‐century climate (Clark et al, 2021; McDowell et al, 2020). Many tree species regenerate through synchronized, highly variable variation in fruit production, termed masting (Fernández‐Martínez et al, 2019; Norden et al, 2007; Pearse et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limitation of our study is that it was based on ordinal rather than continuous seed production data. However, the rapid accumulation of long‐term data on plant reproduction promise further improvements that will allow us to better understand the spatiotemporal patterns of seed production and to hint at processes that may govern those patterns (Fernández‐Martínez et al 2019, Pearse et al 2020, Pesendorfer et al 2020, Clark et al 2021). These data sets already indicate changes in masting intensity and synchrony that are possibly related to climatic change (Redmond et al 2012, Bogdziewicz et al 2020 c , Shibata et al 2020, Hacket‐Pain and Bogdziewicz 2021).…”
Section: Discussionmentioning
confidence: 99%
“…So far, studies are correlational rather than experimental, with causation to climate change inferred. For example, Pearse et al [43] found no relationship between observed changes in CVp and local rates of climate warming across a dataset of 79 species, but this analysis was not able to control for the likely variation in response among species and habitats [98]. Analysis of the within-species masting response to local rates of climate change may prove a useful step forward, particularly where existing species-specific datasets cover gradients in the local rate of climate change.…”
Section: Future Directionsmentioning
confidence: 92%